Identification of amylase activity from vannamei shrimps’ (Litopenaeus vannamei) digestive tract using size exclusion chromatography method - HARIYANTI HARIYANTI; HANIFAH RAHMI (Universitas Syiah Kuala, 2021)
Vannamei shrimps (Litopenaeus vannamei), also known as white leg shrimps are widely cultivated and consumed by many people. However, most consumers have removed the shrimp’s head which integrates with its digestive tract. The digestive tract of white leg shrimp contains digestive enzymes, including amylase. This study aimed to determine the protein content and amylase activity from Vannamei shrimps’ digestive tract using the size exclusion chromatography method. The protein isolation of size exclusion chromatography was prepared in three steps, namely; centrifugation, precipitation, and dialysis. The protein from the dialysis step was purified by using gel filtration chromatography. Each obtained fraction was determined the protein content and amylase activity by using spectrophotometer UV-Vis method. The results showed that the fraction of 108th had the highest protein content and amylase activity with a value of 0.85 mg/ml and 25.66U/ml respectively. @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536869121 1107305727 33554432 0 415 0;p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US;.MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; mso-ansi-language:IN; mso-fareast-language:IN;div.WordSection1 page:WordSection1;